Women empowerment, efficiency and food security nexus in rural Ethiopia: A generalized structural equation modeling - Fentahun Tesafa; Messay Mulugeta; Solomon Tsehay (Heliyon)
Agriculture has been recognized as a key sector to leverage for improved food security. Yet, the evidence on agriculture-gender linkages to food security is still scarce and winding. This study investigates the impact of women empowerment in agriculture on efficiency and food security of households and individuals. Cross-sectional data was collected from 245 women, 80 children and 250 households surveyed in Libokemem district, Ethiopia. Stochastic frontier model was used to determine the level and determinants of efficiency and generalized structural equation modeling to examine empowerment, efficiency and food security nexus. Around 33 % of households, 44 % of women and 28 % of children in the district were food insecure while 64 % of households had adequate levels of women empowerment and their efficiency in crop farming was 65.2 %. This suggests farmers have the potential to increase crop production by about 35 % at existing levels of inputs. Women are disempowered in two major domains including heavy workload and lack of voice in production decisions, which contributed to a marked level of disempowerment at 48 and 22 % respectively. The findings also revealed women empowerment improved dietary diversity and ensured food security for women, children and households. The interaction pathways helped enhance food diversification and better market orientation of farms encouraged these outcomes to increase among all aforementioned groups. However, the adverse implication of efficiency interaction proved to be stronger than its direct positive effect, the efficiency interaction pathway yielded net reduction of these outcomes across all groups. In conclusion, empowering women in agriculture does not just augment market orientation of farmers, it also improves food security of households and vulnerable individuals. This requires interventions specifically targeting those dimensions of disempowerment to increase empowerment to affect the agriculture-food-nutrition nexus positively. Some even suggest gender has a disconnecting/adverse effect on these linkages.